Short communication: Detection of selected agricultural pesticides in river and tap water in Letsitele, Lomati and Vals–Renoster catchments, South Africa - Machete, M; Shadung, JM (Water SA, 2019)
This paper presents the levels of detection of selected agricultural pesticides in river and tap water in the Letsitele, Lomati and Vals–Renoster catchments, South Africa. Agriculture plays a major role in the development of communities through job creation and poverty eradication. However, exposure to agricultural pesticides can result in serious human health and environmental effects. This study, therefore, identified critical areas where specific pesticides might result in high environmental and human health risks. Three water catchment areas, namely, Letsitele, Lomati and Vals–Renoster, were identified for raw and tap water analysis. The results confirmed the presence of selected agricultural pesticides:  atrazine, terbuthylazine, imidacloprid, metolachlor, simazine and alachlor. Although low concentrations of most of these pesticides were detected, pesticides such as atrazine, alachlor and simazine are known for endocrine disruption. A critical finding of this study is the detection of these pesticides in tap water (drinking water) of a primary school in the Lomati catchment. This reveals a high exposure potential for human health. It is thus recommended that further research be conducted to determine the potential health risks associated with these pesticides among vulnerable communities, through epidemiological studies.